The Effect of Mobile Learning on Excretion System Materials on Cognitive Load and Student Concept Mastery - Aulia Nurhamidah Hidayat; Dadang Machmudin; Soesy Asiah Soesilawaty (CV. Dharma Samakta Edukhatulistiwa, 2024)
The fast development of internet and mobile technologies prompt this study. Mobile learning technology is accessible and convenient, as students can use advantageous devices to acquire knowledge at any time and location. Mobile learning can effectively meet students' educational requirements in acquiring knowledge. Furthermore, the design of learning materials that are inappropriate for mobile learning might be attributed to one of the reasons of students' cognitive stress. The purpose of this study is to see how mobile learning (Edmodo) on excretory system content affects cognitive load and student concept mastering. This research used a quasi-experimental method consisting of two classes: the experimental class (using mobile learning) and the control class (conventional learning). The instrument used to measure cognitive load consisted of questionnaires of intrinsic cognitive load, extraneous cognitive, and germane cognitive load, while the instrument for mastery of concepts consisted of pre-test and post-test. In addition, there was also a student response questionnaire to review the use of mobile learning in the experimental class. The data that had been collected were analyzed by a descriptive statistic method using SPSS 25.0. The results show that students in both classes have a cognitive load that can be controlled, but the cognitive load in the experimental class was more controllable than in the control class. The result of mastery of concept showed that the experimental class was higher than the control class, with a post-test significance value of 0.001 <0.05. Thus, it can be concluded that mobile learning influence the excretory system material on the cognitive load and mastery of students' concepts.